Effect of Cardiac-Cycle-Synchronized Selective Vagal Stimulation on Heart Rate and Blood Pressure in Rats. Issue 7 (July 2016) - Plachta, Dennis; Zentner, Josef; Aguirre, Debora; Cota, Oscar; Stieglitz, Thomas; Gierthmuehlen, Mortimer
Abstract Introduction Activation of the baroreflex system through the selective vagal nerve stimulation (sVNS) may become a treatment option for therapy-resistant hypertension, which is a frequently observed problem in the antihypertensive therapy. In previous studies, we used continuous sVNS to lower blood pressure (BP) without major side effects in a rat model. As continuous stimulation is energy consuming and sVNS could be implemented in an antihypertensive stimulator, it was the aim of this study to investigate the efficacy of pulsatile, cardiac-cycle-synchronized sVNS (cssVNS) on the reduction of BP. Methods A multichannel cuff electrode was wrapped around the left vagal nerve in six male Wistar rats under Isoflurane anesthesia. BP was recorded in the left carotid artery. An electrocardiogram (ECG) was obtained via subcutaneous needle electrodes. The aortic depressor nerve fibers in the vagal nerve bundle were selectively stimulated with 18 parameter settings within a window of 15–30 ms after the R-peak in the ECG. The stimulation paradigm included every heartbeat, every second heart beat, and every third heart beat. BP and heart rate were initially recorded over 10 min. Results Using cssVNS, BP could be significantly reduced over 30 min and maintained at this level. While the highest BP reduction was seen during cssVNS at every heartbeat with minimal bradycardia, less—yet significant—BP reduction was seen during cssVNS at every second or third heartbeat without causing detectable bradycardia. Conclusion cssVNS can chronically reduce BP in rats avoiding measurable bradycardic side effects. This energy-efficient technique might allow the implementation of sVNS using an implantable device to permanently lower BP in patients. Funding The study was funded by Bundesministerium fur Bildung und Forschung/German Federal Ministry of Education and Research among the call "Individualisierte Medizintechnik" under the grant number FKZ 13GW0120B.